Abonos orgánicos como alternativa para el mejoramiento y conservación de suelos afectados por el incorrecto manejo de pesticidas agrícolas - Acosta Ramos, Jeffrey Arturo (2022)
In this document, organic fertilizers were investigated as an alternative for the improvement and conservation of soils affected by the incorrect management of agricultural pesticides. The environmental contamination produced by pesticides is mainly due to direct applications on agricultural crops, their inappropriate use by the population and the lack of knowledge of the problems that these chemicals can cause in the soil. This study is carried out to demonstrate how organic fertilizers can help us by counteracting the damage caused by the incorrect handling of chemical products in agricultural fields, thus obtaining the benefits that organically treated soil gives us. This investigative document, presented as a practical component, was developed through the collection of all kinds of information, carrying out a detailed investigation in the different free access web pages, scientific articles, thesis, sources and bibliographic documentation available on different platforms. digital. The main findings were that the application of organic fertilizers or biofertilizers allows the maintenance and recovery of the physical, chemical, and biological properties of the soil. It was concluded that the benefits of organic fertilizers in the soil can be physical, chemical, and biological. In the physical part, they improve the structure of the soil and increase its moisture retention capacity. In the chemical part, it improves the cation exchange capacity and reduces the acidity of the soil. And finally, in the biological part, the beneficial microorganisms present in the soil increase, significantly reducing the activity of pathogens and increasing the content of organic matter.